In silico virtual screening of lead compounds for major antigenic sites in respiratory syncytial virus fusion protein - Shilu Mathew (625826) (2022)
Human respiratory syncytial virus (RSV) is a leading ubiquitous respiratory pathogen in newborn infants, young children, and the elderly, with no vaccine available to date. The viral fusion glycoprotein (RSV F) plays an essential role in the infection process, and it is a primary target of neutralizing antibodies, making it an attractive site for vaccine development. With this in view, there is a persistent need to identify selective antiviral drugs against RSV, targeting the major antigenic sites on the F protein. We aimed to conduct a robust in silico high-throughput drug screening of one million compounds to explore potential inhibitors that bind the major antigenic site Ø and site II on RSV F protein, which are the main target of neutralizing antibodies (NAb). We utilized the three-dimensional crystallographic structure of both antigenic site Ø on pre-F and antigenic II on post-F to screen for potential anti-RSV inhibitors. A library of one million small compounds was docked to explore lead binders in the major antigenic sites by using virtual lab bench CLC Drug Discovery. We also performed Quantitative Structure-Activity and Relationship (QSAR) for the lead best binders known for their antiviral activity. Among one million tested ligands, seven ligands (PubChem ID: 3714418, 24787350, 49828911, 24802036, 79824892, 49726463, and 3139884) were identified as the best binders to neutralizing epitopes site Ø and four ligands (PubChem ID: 865999, 17505357, 24802036, and 24285058) to neutralizing epitopes site II, respectively. These binders exhibited significant interactions with neutralizing epitopes on RSV F, with an average of six H bonds, docking energy of − 15.43 Kcal·mol−1, and minimum interaction energy of − 7.45 Kcal·mol−1. Using in silico virtual screening, we identified potential RSV inhibitors that bind two major antigenic sites on the RSV F protein. Using structure-based design and combination-based drug therapy, identified molecules could be modified to generate the next generation anti-RSV drugs. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-021-00213-6